Recent developments in cryptocurrency markets: Co-movements, spillovers and forecasting - Thanasēs Stengos (Journal of Risk and Financial Management, 2021)
The emergence of Bitcoin and other cryptocurrencies has led to an explosion of trading and speculation in once nontraditional markets [...]
Keywords: 330